Great Expectations? Antecedents of Women Farmers' Willingness to Participate in Agricultural Education Programmes. (September 2013) - Charatsari, Chrysanthi; Papadaki-Klavdianou, Afroditi; Michailidis, Anastasios; Partalidou, Maria
The aim of this research was to identify the factors affecting women farmers' participation in agricultural education programmes (AEPs) and to investigate the motives and expectations that influence women's willingness to participate in AEPs. Data were drawn from a random sample of women farmers from northern Greece, while a witness sample of male farmers was used to test the moderating effect of gender on the motivation to participate in AEPs. The results of multivariate analysis indicate that the most crucial parameters in the prediction of women's participation in AEPs are those reflecting their level of involvement in agriculture. Compared with men, women farmers report significantly higher levels of motivation to participate in AEPs deriving from self-actualization needs. Interestingly, the findings reveal that the expectation of gaining economic benefits is a far less important predictor of willingness to attend AEPs. The implications for agricultural education administrators, limitations and future research directions are noted.